Structure parameter optimization and bearing limit analysis of the expansion unit of three-roller tube expander. Issue 5 (13th May 2020) - Bi, Gang; Qu, Zhan; Wang, Zhenquan; Dou, Liangbin; Li, Mengmeng
Abstract : The critical technical issues for the structure design of three-roller tube expander were first studied and analysed in this paper. Then, the major design parameters of the expansion unit structure and the bearing limit of 12¼″ three-roller tube expander were optimized and investigated by finite-element numerical simulation method. Results from study show that the required expansion force increases when the taper angle of the roller outer surface gets larger, taking the axial expansion force as the quantitative indicators. It is suggested that the roller tape angle of the expansion unit should be in the range of 9–12° considering the proper length of the roller and the non-self-locking tube expansion process. The required expansion force of the bellows first decreases and then increases when the gauge length of the expansion unit becomes longer. The optimal value of the gauge length is 50 mm considering the proper length of the roller. And according to the numerical simulation results, the designed three-roller tube expander meets the strength requirements. The results of this study are of great significance to the expend bellows drilling technology.